(untitled) (Journal of Computational Innovation and Analytics (JCIA), 2025)
The market landscape is marked by intense competition, necessitating continuous product enhancements, particularly within the food sector. To meet evolving consumer demands and adapt to changing consumption patterns, the marketing mix serves as a strategic tool to foster profitable relationships rooted in consumer satisfaction and loyalty. This study aims to investigate the impact of the marketing mix on consumer satisfaction with parboiled rice and to examine its influence on repurchase intentions. Data were collected from 300 respondents and analyzed using PLS-SEM. Findings indicate that marketing mix elements; product, price, place, and promotion, positively and significantly influence consumer satisfaction. However, the relationship between these variables and repurchase intentions varied. The final model supports the connection between satisfaction and the intention to repurchase. Product attributes, such as the health benefits of parboiled rice, play a crucial role, alongside the significance of the sales location. Remarkably, there was no evidence to support the notion that price and repurchase intention were related, and promotion had a negative correlation with repurchase intention, which calls for more research. These insights are invaluable for parboiled rice producers and marketing managers, highlighting the need to enhance these product aspects to boost consumer engagement and loyalty.